Back Cover: Spectral Imaging to Measure Heterogeneity in Membrane Lipid Packing (ChemPhysChem 7/2015). Issue 7 (18th May 2015) - Sezgin, Erdinc; Waithe, Dominic; Bernardino de la Serna, Jorge; Eggeling, Christian
<x xml:space="preserve">Abstract</x> When spectral imaging is combined with advanced image analysis it provides an excellent tool to tackle the long‐standing questions concerning membrane lateral heterogeneity, as described by E. Sezgin, C. Eggeling et al., on p. 1387.